iTrans: an Intelligent Transportation Management Platform for Efficient and Equitable Paratransit Services - Aleixo Domingues, Carlos (Humanas em Perspectiva, 2024)
This new ebook produced by researcher Carlos Aleixo Domingues demonstrates how technology can improve traffic in cities, and also allow for effective management of public bodies.